Evaluation of water quality, selected metals and endocrine-disrupting compounds in the rivers and municipal wastewaters of Eastern Cape Province, South africa - Farounbi, Adebayo Ibikunle (Rhodes University, Faculty of Pharmacy, Pharmacy)
South Africa is developing with increasing population, and so is the demand for use and access to water resources. Surface water is critical to the country because it provides about 77% of the needed water resources. Low rainfall (about 450 mm annually) with little runoffs to boost the rivers aggravates the problems of surface waters. Expansion of industrial and agricultural activities coupled with the population pressure had an impact on water quality, availability and the state of aquatic ecosystems in the country. Water management is a challenge in South Africa because of the socio-economic pressure and other factors such as mine wastewater, eutrophication, salinisation, and emerging contaminants. This research investigated some water quality parameters of Bloukrans, Buffalo, Swartkops and Tyhume Rivers in Eastern Cape Province of South Africa for three seasons. The parameters investigated include the physicochemical properties, functional groups of organic compounds, presence of endocrine-disrupting compounds and heavy metals in the rivers and wastewater effluents from wastewater treatment plants (WWTPs) released into these rivers. The aims were to determine the concentrations of these parameters in the rivers and wastewater effluents, compare the concentration levels with recommended values for aquatic lives, domestic and agricultural purposes, thereby contributing to the effective management of water in South Africa. Water samples were collected for analyses at upstream, midstream and downstream reaches of the rivers. In contrast, wastewater influent and effluent samples were obtained from wastewater treatment plants releasing effluents to the rivers. Some physicochemical parameters were studied onsite with specialised meters while others analysed in the laboratory with ultraviolet (UV) spectroscopy. Chemical functional groups in the samples were determined with Fourier-transformed infrared (FT-IR) and nuclear magnetic resonance (NMR) spectroscopies. The Endocrine-disrupting compounds and heavy metals were determined with liquid chromatography coupled to a mass spectrometer (LC-MS/MS) and inductively coupled plasma with a mass spectrometer (ICP-MS) respectively. Method validation and calibration for all the spectrometry yielded good linearity (r2 > 0.99). The results showed high oxygen demand above the concentration recommended by the South Africa Department of water affairs and forestry (DWAF) for Alice and Uitenhage wastewater effluents, midstream and downstream river samples. Phosphate concentrations were higher than the recommended level in wastewater effluents. Sulphate rivers at midstream and downstream reaches were higher than 8.0 except in Bloukrans River, where it was around 7.0. The functional group analyses show the presence of substituted aromatic compounds, alkyl halides, chlorobenzenes, vinylidenes, amides, amines, urethanes, cycloalkanes, acetonitriles, methenamine, imidazole and phenolic compounds among others, in the samples. The presence of these functional groups in the water samples is an indication of pollution by volatile organic compounds, persistent organic pollutants and pharmaceuticals. Results of LC-MS/MS analysis show that endocrine-disrupting compounds (EDCs) were present in the rivers and wastewaters samples. Descriptive statistics showed the mean concentrations of the EDCs in the samples as nonylphenol > dichlorophenol > bisphenol A > triclosan > octylphenol > imidazole > atrazine > triazole > estrone > estradiol. The results of the heavy metal analysis show that chromium had the highest mean concentration in the samples. The mean metals concentrations in the samples were in the order of Cr > Ni > Mn > Cu > As > Pb > Cd > Hg > Zn. The results showed an increase in the concentrations of metals in the rivers over the years. The chromium, manganese, nickel, copper, zinc, arsenic, cadmium, lead and mercury concentrations in the lower reaches of the rivers and wastewater effluents were higher than the values recommended by the United Nations Environmental Programme (UNEP) and DWAF. Improvement is necessary in wastewater treatment and adequate legislation on chemical usage. Some chemicals banned in developed countries, such as atrazine, were encountered in this study.
Keywords: Water Pollution -- South Africa -- Eastern Cape; Wastewater treatment; Endocrine disrupting chemicals; Heavy metals; Mass spectrometry; Physicochemical process; Nuclear magnetic resonance; Infrared spectroscopy